An experimental approach to assess the post-depositional mobility of 134Cs. (December 2021) - Bam, Wokil; Teyssié, Jean-Louis; Metian, Marc; Oberhaensli, François; Maiti, Kanchan; Swarzenski, Peter W.
Abstract: The partitioning coefficient, Kd, which is defined by the reversible sorption processes between a solid and an aqueous phase at equilibrium, is one of the most important parameters to assess environmental transport and risk. In this study, a series of simple laboratory experiments were conducted to investigate sorption properties of 134 Cs on a model sediment under two treatments ( shaken vs non-shaken ) and with three ( small : <75 μm, large : > 75 μm and bulk i.e., composite) particle size fractions. Vertical transport of 134 Cs across the water-sediment interface and into sediment was also evaluated. As expected, grain size had the strongest influence on 134 Cs Kd values, with the small particle size fraction yielding significantly higher Kd values than the large and bulk fractions. The mean Kd values obtained from the various experiments ranged from 89 ± 13–130 ± 5 L kg −1 ( small), 44 ± 10–91 ± 13 L kg −1 ( large), 73 ± 3–112 ± 11 L kg −1 ( bulk, shaken) and 73 ± 5–110 ± 4 L kg −1 ( bulk, non-shaken) . Most of the 134 Cs partitioning processes occurred rapidly (<2 h) into the experiment. Physical mixing ( shaken ) did not appear to significantly affect the 134 Cs Kd values. In complement, a separate experiment on the vertical penetration of 134 Cs into a bulk sediment column showed that 134 Cs was able to penetrate up to 5 cm into the sediment column after 88 days (∼0.6 mm d −1 ) and this flux rate is comparable to natural settings. Adsorption and contact time were found to be key for the 134 Cs penetration process. Results from these experiments add to the literature on post-event radionuclide transport studies in marine settings and provide an experimental perspective that can be built upon to complement field observations. Graphical abstract: Image 1 Highlights: Physical mixing ( shaken ) did not appear to significantly affect the 134 Cs Kd values. 134 Cs vertically penetrated upto 5 cm deep after 88 days (∼0.6 mm d −1 ) and this flux is comparable to natural setting. Adsorption and contact time were found to be key for the 134 Cs penetration process.